Mortality in hepatobiliarypancreatic surgery. - Carriquiry, Guillermo; Beguiristain, Alberto; González, Jorge; Colet, Andrés; Estefan, Alberto (Cirugía del Uruguay, 1984)
Authors make an statistical analysis of 41 patients deceased out of a series of 763 patients undergoing bi· liary surgery. The overall mortality rate was 5,5, % . The 84,5% of deceased patients were over 60 years. In 65,8 % of the cases, icteritia was found. Twenty pa· tients (48,8%) showed exclusive benign pathology and 21 (51,2%) malignant pathology.